PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP AKHLAK PESERTA DIDIK DI SMA UII YOGYAKARTA - Suwahyu, Irwansyah (Rabbani: Jurnal Pendidikan Agama Islam, 2023)
This study examines how the use of social media by students at SMA UII Yogyakarta affects their morals. The method used in this study is a combination method or mixed methods. Where the design uses a sequential explanatory model. This study reveals in advance how often students use social media through a quantitative approach by analyzing the results of student questionnaires. And then describe it using a qualitative approach. The result of this study is that the level of students' use of social media is 80%. And when it is associated with morals, the behavior is positive. However, in an in-depth study through interview questions and observations made on students' social media accounts, negative things were found. So it can be concluded that social media that is used too often will have a negative impact on the morals of students.